Editorial: Pannexin‐1—the hidden gatekeeper for HIV‐1. Issue 3 (1st September 2013) - Paoletti, Audrey; Raza, Syed Qasim; Voisin, Laurent; Law, Frédéric; Caillet, Marina; Martins, Isabelle; Deutsch, Eric; Perfettini, Jean‐Luc
Abstract : Discussion on the hemichannel PANX1 and associated signaling molecules as new targets for the development of anti‐HIV therapeutic strategies.